2020
DOI: 10.2151/sola.2020-036
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of Atmospheric Aerosol Particles Focused on Cloud Condensation Nuclei and Ice Nucleating Particles from Ground-Based Observations in Tsukuba, Japan

Abstract: This is a PDF of a manuscript that has been peer-reviewed and accepted for publication. As the article has not yet been formatted, copy edited or proofread, the final published version may be different from the early online release. This pre-publication manuscript may be downloaded, distributed and used under the provisions of the Creative Commons Attribution 4.0 International (CC BY 4.0) license. It may be cited using the DOI below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Aerosols can be transported from their sources, which include natural (e.g., volcanos, dust, ocean) and anthropogenic emissions, to different locations and are susceptible to environmental and weather conditions. Other studies have shown that aerosols and their optical properties in a particular area show seasonality (Humphries et al, 2023;Orikasa et al, 2020;Jain et al, 2020;Cigánková et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Aerosols can be transported from their sources, which include natural (e.g., volcanos, dust, ocean) and anthropogenic emissions, to different locations and are susceptible to environmental and weather conditions. Other studies have shown that aerosols and their optical properties in a particular area show seasonality (Humphries et al, 2023;Orikasa et al, 2020;Jain et al, 2020;Cigánková et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Anthropogenic aerosols contain a very complicated mixture of elemental carbon, organic, and inorganic materials. Recent studies have found that anthropogenic aerosols have lower INAS density than dust particles at temperatures below −15°C (Bi et al., 2019; Orikasa et al., 2020).…”
Section: Introductionmentioning
confidence: 99%